Protecting capacity against malaria of chemically defined tetramer forms based on the Plasmodium falciparum apical sushi protein as potential vaccine components (2014)
Developing novel generations of subunit-based antimalarial vaccines in the form of chemically-defined macromolecule systems for multiple antigen presentation represents a classical problem in the field of vaccine development. Many efforts involving synthesis strategies leading to macromolecule constructs have been based on dendrimer-like systems, the condensation of large building blocks and conventional asymmetric double dimer constructs, all based on lysine cores. This work describes novel symmetric double dimer and condensed linear constructs for presenting selected peptide multi-copies from the apical sushi protein expressed in Plasmodium falciparum. These molecules have been proved to be safe and innocuous, highly antigenic and have shown strong protective efficacy in rodents challenged with two Plasmodium species. Insights into systematic design, synthesis and characterisation have led to such novel antigen systems being used as potential platforms for developing new anti-malarial vaccine candidates. © 2014 Elsevier Inc. All rights reserved.